Protection From Varicella Zoster in Solid Organ Transplant Recipients Carrying Killer Cell Immunoglobulin-Like Receptor B Haplotypes. Issue 12 (December 2015) - Schmied, Laurent; Terszowski, Grzegorz; Gonzalez, Asensio; Schmitter, Karin; Hirsch, Hans H.; Garzoni, Christian; van Delden, Christian; Boggian, Katia; Mueller, Nicolas J.; Berger, Christoph; Villard, Jean; Manuel, Oriol; et al.
Abstract : Background: Natural killer cell function is regulated by inhibitory and activating killer cell immunoglobulin-like receptors (KIR). Previous studies have documented associations of KIR genotype with the risk of cytomegalovirus (CMV) replication after solid organ transplantation. Methods: In this study of 649 solid organ transplant recipients, followed prospectively for infectious disease events within the Swiss Transplant Cohort Study, we were interested to see if KIR genotype associated with virus infections other than CMV. Result: We found that KIR B haplotypes (which have previously been linked to protection from CMV replication) were associated with protection from varicella zoster virus infection (hazard ratio, 0.43; 95% confidence interval, 0.21-0.91; P = 0.03). No significant associations were detected regarding the risk of herpes simplex, Epstein-Barr virus or BK polyomavirus infections. Conclusions: In conclusion, these data provide evidence that the relative protection of KIR haplotype B from viral replication after solid organ transplantation may extend beyond CMV to other herpes viruses, such as varicella zoster virus and possibly Epstein-Barr virus. Abstract : Solid organ transplant recipients with KIR B haplotypes are associated with protection from cytomegalovirus. This study shows that they area also associated with protection from varicella zoster infection, but not Epstein-Barr virus (another herpes virus) or BK, a polyomavirus.